2013
DOI: 10.7314/apjcp.2013.14.11.6507
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A1 Genetic Polymorphisms and Risk for Esophageal Cancer: a Case-control Study in Central China

Abstract: The purpose of this study was to evaluate the associations of CYP1A1 genetic polymorphisms with the risk of developing esophageal cancer (EC). A case-control study was carried out in a Chinese population in which 157 hospital based EC cases and 157 population based healthy controls with 1:1 match by age and sex were included. PCR based restriction fragment length polymorphisms (PCR-RFLP) were used to detect genotypes in case and control groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Data from a meta-analysis study on lung cancer, drawing from 13 existing studies comprising of subjects from Japan, China, Korea and Thailand found that the prevalence of C allele is around 42.4% (Lee et al, 2008). More recently, a study on lung cancer in the Inner Mongolia region reported with a high level of the C allele (~50%) (Jiang et al, 2014) whereas a different study on esophageal cancer in Central China reported that the C/C genotype in China to be around ~37% (Yun et al, 2013). Both our data and the findings from these studies seem to be in concurrence whereby the prevalence of C alleles within Asian populations is generally around 35% to 50%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from a meta-analysis study on lung cancer, drawing from 13 existing studies comprising of subjects from Japan, China, Korea and Thailand found that the prevalence of C allele is around 42.4% (Lee et al, 2008). More recently, a study on lung cancer in the Inner Mongolia region reported with a high level of the C allele (~50%) (Jiang et al, 2014) whereas a different study on esophageal cancer in Central China reported that the C/C genotype in China to be around ~37% (Yun et al, 2013). Both our data and the findings from these studies seem to be in concurrence whereby the prevalence of C alleles within Asian populations is generally around 35% to 50%.…”
Section: Discussionmentioning
confidence: 99%
“…A single nucleotide polymorphism (SNP) of CYP1A1 at position 3801 in the 3' untranslated region results in a change of a T to C base (Spurr et al, 1987). Consequently, this resulting MspI polymorphism has been extensively studied alongside numerous malignancies including cervical carcinoma, esophageal carcinoma, oral carcinoma, breast carcinoma, colorectal cancer and lung carcinoma (Sivaraman et al, 1994;Tanimoto et al, 1999;Kim et al, 2000;Goodman et al, 2001;Boyapati et al, 2005;Joseph et al, 2006;Agorastos et al, 2007;Juarez-Cedillo et al, 2007;Nishino et al, 2008;Gutman et al, 2009;Chen et al, 2011;von Keyserling et al, 2011;Sergentanis et al, 2012;Shukla et al, 2012;Zhuo et al, 2012a;Zhuo et al, 2012b;Ding et al, 2013;Islam et al, 2013;Liu et al, 2013;Saeed et al, 2013;Shukla et al, 2013;Xia et al, 2013;Yun et al, 2013;Jiang et al, 2014). The association between this CYP1A1 polymorphism with cervical carcinoma has been examined previously in various populations, with mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…The confirmed carcinogenic species reported in tobacco mainly include nitrosamines, aromatic amines and polyaromatic hydrocarbons (PAH) (Yun et al, 2013). Tobacco use and alcoholism have also been shown to possess synergistic effects increasing the relative risk over 100-times than that of induced by tobacco or alcohol use alone.…”
Section: Introductionmentioning
confidence: 99%
“…After extracting the DNAg, it was amplified by polymerase chain reaction and subsequent digestion with restriction enzymes (Lee et al 2006;Yun et al 2014).…”
Section: Genotypic Analysismentioning
confidence: 99%